A mode of developing financial service innovation management for digital finance in property insurance business - data from insurance companies in Guangdong province, China - Zhong, Jiali; Sukpasjaroen, Khunanan (Edelweiss Applied Science and Technology, 2025)
For the insurance industry with strong data dependence, insurance companies urgently need to accelerate the process of digital transformation and improve the financial service innovation management of insurance companies through digital finance and precision marketing. Therefore, the objectives of this research were (1) to study the current situation of global and Chinese digital financial innovation service management; (2) to analyze the factors affecting the property insurance business in Guangdong, China; (3) to propose a management model for financial business service innovation. Guided by constructivism and positivism methodology, this study uses qualitative and quantitative analysis and conducts empirical research. The first study recruited 30 participants to conduct in-depth interviews. The second study used questionnaires to obtain 833 valid responses. Advanced statistical software was used for the analysis of the survey data. This paper draws the following conclusions: (1) digital finance has a role in improving innovation management; (2) precision marketing has an improving effect on innovation management; (3) precision marketing has a partial intermediary role between digital finance and the innovation management of property insurance companies. Based on these findings, this study proposes the theoretical framework of digital finance, precision marketing, and financial service innovation management. This research provides decision support to the management of insurance companies and is of great significance for insurance companies to continuously promote digital finance and precision marketing and improve financial service innovation management. At the same time, it also provides a reference for the improvement and sustainable development of financial service innovation management of similar insurance companies.